Bridge to heart transplantation in patients with cardiogenic shock: a 20-year experience with two different surgical strategies. Issue 5 (May 2021) - Sponga, Sandro; Nagpal, A. Dave; Vendramin, Igor; Ferrara, Veronica; Lechiancole, Andrea; Maiani, Massimo; Nalli, Chiara; Di Nora, Concetta; Guzzi, Giorgio; De Manna, Nunzio D.; Bortolotti, Uberto; Livi, Ugolino
Abstract : Aims: We aimed to describe how treatment of patients in cardiogenic shock bridged to heart transplantation with mechanical circulatory support, using either biventricular assist devices (BVADs) or extracorporeal life support (ECLS), has evolved in the last 20 years in our centre. Methods: Since 1998, 72 patients with refractory heart failure and indication for heart transplantation have received mechanical circulatory support: 40 had an ECLS system and 32 a BVAD. Results: Early mortality was similar (17.5 vs. 9.4%, P = 0.25) regardless of the type of support. After a median support time of 8 (1–27) vs. 34 (0–385) days ( P < 0.01), 70 vs. 65.6% ( P = 0.69) of patients underwent transplantation in the two groups. Prior to transplantation, BVAD patients were more stable with lower need for mechanical ventilation (9 vs. 57%, P < 0.01) and dialysis (0 vs. 38%, P < 0.01). Thirty-day mortality after transplantation was similar (18 vs. 14%, P = 0.53). Patients with extracorporeal support had higher rates of renal ( P = 0.02) and respiratory failure ( P = 0.03), infections ( P = 0.02), atrial fibrillation ( P = 0.03) and longer ICU stay ( P = 0.01). Late survival was similar, while 5-year freedom from coronary vasculopathy was higher in those with BVAD ( P = 0.03). Conclusion: Although ECLS provides faster and simpler assistance compared with BVADs, no differences in early and medium-term outcomes in the last 20 years were observed in patients with cardiogenic shock. However, BVADs provided longer duration of support, better multiorgan recovery allowing more adequate graft selection, resulting in a lower rate of posttransplant complications.